Treasury's medium-term economic projection methodology - Jared Bullen; Jacinta Greenwell; Michael Kouparitsas; David Muller; John O'Leary; Rhett Wilcox (The Australian Government, The Treasury, 2014)
Treasury's forecasting framework has evolved over the past 21 years from the outlook for a single financial year to the outlook for the Australian economy 40 years ahead for intergenerational analysis. A constant through this evolution has been the sharp distinction between the methodologies used for near and longer term forecasts. The economic estimates underlying Australian Government fiscal projections divide the forecast horizon into two distinct periods: the near term forecast period which covers the first two years beyond the current financial year; and the longer term projection period which includes the last two years of the forward estimates, and up to 36 more years for intergenerational analysis. The economic estimates over the forecast period are based on a range of short run forecasting methodologies, while those over the projection period are based on medium to long run rules. Treasury routinely assesses medium to long run projection rules in light of new data, improved modelling techniques and structural changes to the economy. The measured cyclical weakness of recent years calls for an enhancement to the existing trend growth rate rules, which recognises the need for an adjustment period over which the economy transitions from a cyclical high or low to its potential level of output. Working towards that end, this paper details changes to the projection methodology that overcome the cyclical limitations of the existing framework. Applying these methodological changes to the economic estimates in the 2014 15 Budget leads to a slight improvement in the Underlying Cash Balance of 0.9 billion (0.05 per cent of GDP) in 2017 18 and 3.4 billion (0.12 per cent of GDP) in 2024 25.
Keywords: E30; E66; H68; 330; potential output; NAIRU; fiscal budget